The Preparation and Reactions of Aryltin Pentachlorophenoxides - Bhattacharya, S.N.; S. Pakdaman, Ahmad (Asian Journal of Chemistry, 2010)
The preparation of aryltin pentachlorophenoxides (C6H5)2SnOC6Cl5; (p-CH3C6H4)3SnOC6Cl5 and (C6H5)2Sn(OC6O5Cl5)2 are given along with their reactions with unsaturated substrates (C6H5N═C═O, S═C═S, O═S═O) which add across the Sn-O bond of the alkoxides. The products have been identified and the details of reactions discussed.